Microstructure and Properties of CoCrFeMnNiMox High-Entropy Alloy Coating by Laser Cladding - LIU Hao, SUN Shifeng, LI Xiaojia, HAO Jingbin, YANG Haifeng (Shanghai Jiaotong Daxue xuebao, 2022)
45 steel has the problems of low wear resistance and poor corrosion resistance. CoCrFeMnNiMox (x=0.00, 0.25, 0.50, 0.75, 1.00) high-entropy alloy coating was prepared on 45 steel by laser cladding. The influence of Mo on the microstructure and properties of coating were explored in detail. The results show that the CoCrFeMnNiMox high-entropy alloy coating is composed of a single face-centered cubic (FCC)solid-solution phase. The microstructure of the Mo-containing coating is a typical dendritic and interdendritic structure, which is caused by the heterogeneous nucleation of the molten pool during the solidification process. The microhardness of the coating increases with the increase of x, and the maximum microhardness of the Mo1.00 coating is 2.391 GPa. Quantitative calculations show that solution strengthening is the main reason for the increase of microhardness. With the increase of Mo mass fraction, the wear mechanism evolves from adhesive wear to abrasive wear and oxidative wear. The Mo1.00 coating has the lowest volume wear rate (0.68×10-4 mm3/(N·m)). The influence of the passivation process on the corrosion resistance of coating was analyzed based on the point defect model theory. The addition of the Mo element increases the dehydration rate of the passivation behavior of coating, which makes the oxide layer thicker, and thereby improving the corrosion resistance of coating. The corrosion mechanism of coatings is intergranular corrosion. Mo0.75 coating has the smallest self-corrosion current density and the most positive self-corrosion potential, which are 3.69×10-6 A/cm2 and -0.432 V, respectively.